New piezoelectric sensors with Gall Bladder stone material. (29th June 2009) - Singh, V.R.; Singh, Kanika
Gall Bladder (GB) stones are studied as new sensor materials for biomedical and other applications. The GB material samples are analysed for knowing their chemical composition by using an X-Ray diffractometry and other techniques. α-Quartz is found to be present prominently in these stones to exhibit their piezoelectric (PZT) property, which is utilised to develop new PZT sensors for biomedical and other applications. This is an expanded version of a paper presented at the 3rd IEEE International Workshop on Medical Measurements and Applications, 9?10 May 2008, Ottawa, ON, Canada.